Diagnosis of invasive fungal diseases in pediatric patients. Issue 12 (1st December 2016) - Pana, Zoi-Dorothea; Vikelouda, Katerina; Roilides, Emmanuel
ABSTRACT: Introduction : The optimal management of invasive fungal infections (IFIs) in children requires prompt and precise diagnosis that enables timely implementation of appropriate antifungal therapy and decreased use of unnecessary toxic antifungals. Areas covered : Traditional approaches such as culture, microscopy and histopathology remain the gold standard but are often not sufficiently sensitive and specific. These limitations have led to the development of alternative non-invasive diagnostic methods that in most cases detect fungal components, such as antigens or nucleic acids. To date, galactomannan and 1, 3 β-D-glucan assays are the most efficient non-culture methods for diagnosis and monitoring of antifungal therapy. New technologies from nano-sciences are applied, like T2Candida assay. However, these are not standardized or validated in children. Herein, we focus on IFI diagnosis emphasizing current perspectives, interpretation difficulties, and need for further evaluation in pediatrics. Expert commentary : The new diagnostic tools may enhance diagnostic capacity in combination with traditional methods.